PERTANGGUNG JAWABAN PIDANA MENGEDARKAN PESTISIDA TIDAK SESUAI DENGAN LABEL - RAYENDRA SATHYA WIBISANA (Fakultas Hukum Universitas Narotama, 2020)
This study discusses the issue of whether the criminal sanctions against the perpetrators who distribute pesticides are not in accordance with the label and whether the legal considerations of the Tebingtinggi District Court No. 650 / Pid.B / 2015 / PN Tbt, is in accordance with Law Number 20 of 2016 concerning Marks and Geographical Indications. Research with a statutory regulatory approach and conceptual approach, a conclusion is obtained that the criminal sanctions against the perpetrator who circulates pesticides are not in accordance with the label, that producing and trading goods that are not in accordance with what is stated on the label, it can be said to have committed an illegal act, namely violating the provisions of Article 60 paragraph (1) letter g of Law no. 12 of 1992, prohibits the distribution of pesticides that are not registered and do not comply with the label. The government prohibits the procurement, distribution and planting of certain plant seeds that are detrimental to the community, plant cultivation, other natural resources, and / or the environment. Legal considerations of the Tebingtinggi District Court decision No. 650 / Pid.B / 2015 / PN Tbt, in accordance with Law No. 15 of 2001, that YN's action to produce grass-fighting drugs or weeds (herbicides) uses the original Basmilang 480 SL brand and label produced by PT. Petro Kimia Kayaku, has fulfilled all the elements of Article 90 of Law no. 15 of 2001, then he is subject to a criminal sanction in the form of imprisonment for a maximum of 5 (five) years and / or a maximum fine of Rp. 1,000,000,000.00 (one billion rupiah). This decision was based on the consideration that YN's actions had fulfilled all the elements of Article 90 of Law no. 15 of 2001. Keywords: Criminal Liability, Circulating Pesticides, Not In Accordance With Labels